Characteristics of the legislative branch in the USA - Turchynov , Kyrylo (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
This article is dedicated to exploring the peculiarities of the legislative branch in the United States of America (USA). The author extensively examines the role and functions of Congress as a significant legislative body in the system of checks and balances in the country. The article sheds light on the process of passing laws at the federal level, starting from the introduction of bills to their adoption and presidential signing. Special attention is given to the role of committees in the legislative process, the procedures of bill consideration and discussion in the chambers of Congress, as well as the interaction between different branches of government in the process of lawmaking. The author also analyzes the mechanisms for oversight and control over the executive branch, including the impeachment process, which makes the legislative power a crucial player in the internal politics of the USA. A comprehensive overview of the legislative process in the United States helps better understand the country's political system and its functioning mechanisms.